A case-study to examine doctors’ intentions to use IoT healthcare devices in Iraq during COVID-19 pandemic - Alhasan, Ameer; Audah, Lukman; Ibrahim, Ishaq; Al-Sharaa, Ammar; Al-Ogaili, Ali Saadon; M. Mohammed, Jabiry (International journal of pervasive computing and communications, 2022)
PurposeSeveral countries have been using internet of things (IoT) devices in the healthcare sector to combat COVID-19. Therefore, this study aims to examine the doctors’ intentions to use IoT healthcare devices in Iraq during the COVID-19 pandemic.Design/methodology/approachThis study proposed a model based on the integration of the innovation diffusion theory (IDT). This included compatibility, trialability and image and a set of exogenous factors such as computer self-efficacy, privacy and cost into the technology acceptance model comprising perceived ease of use, perceived usefulness, attitude and behavioral intention to use.FindingsThe findings revealed that compatibility and image of the IDT factors, have a significant impact on the perceived ease of use, perceived usefulness and behavioral intention, but trialability has a significant impact on perceived ease of use, perceived usefulness and insignificant impact on behavioral intention. Additionally, external factors such as privacy and cost significantly impacted doctors’ behavioral intention to use. Moreover, doctors’ computer self-efficacy significantly influenced the perceived ease of use, perceived usefulness and behavioral intention to use. Furthermore, perceived ease of use has a significant impact on perceived usefulness and attitude, perceived usefulness has a significant impact on attitude, which, in turn, significantly impacting doctors' behavior toward an intention to use.Research limitations/implicationsThe limitations of the present study are the retractions of the number of participants and the lack of qualitative methods.Originality/valueThe finding of this study could benefit researchers, doctors and policymakers in the adaption of IoT technologies in the health sectors, especially in developing counties.